Evaluasi dan Penilaian Pembelajaran dari Perspektif Standar Nasional Pendidikan - Destiana Eka Putri; Nurul Fatimah; Siti Nur Kholifah; Sofyan Iskandar (STAI AL-AMIN, 2025)
This research aims to understand the concepts, principles and types of learning evaluation and its role in improving the quality of education. The method used is a literature study with content analysis from various sources such as books, journals and national education regulations. The data collected includes the definition of evaluation, purpose, function, basic principles, types of evaluation, and national assessment standards. The results showed that evaluation conducted systematically, objectively and continuously can provide a comprehensive picture of the achievement of learning objectives and the effectiveness of the teaching and learning process. Formative, summative, portfolio and authentic evaluations play an important role in measuring students' cognitive, affective and psychomotor aspects. National standards ensure professional and accountable evaluation. In conclusion, proper understanding and implementation of evaluation can improve the quality of learning and support effective educational decision-making. This research is expected to be a reference for educators in designing valid and reliable assessments.